The Influence of Organizational Culture and Leadership on Employee Performance at Wirobrajan District Office Yogyakarta City - Dian Lestari; Nany Noor Kurniyati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze and identify the influence of organizational culture and leadership on employee performance at the Wirobrajan District Office, Yogyakarta City. The independent variables examined include organizational culture (X1) and leadership (X2), while the dependent variable is employee performance (Y). A quantitative approach with an associative research type was employed. The entire population of 45 employees was used as the research sample through a saturated sampling method. Data were collected using questionnaires and analyzed using multiple linear regression techniques. The results show that both organizational culture and leadership have a positive and significant partial influence on employee performance. Simultaneously, both variables also have a significant effect on performance. The regression coefficient values indicate that organizational culture has a more dominant influence compared to leadership. Furthermore, the adjusted R² value of 55.7% indicates that the variation in employee performance can be explained by the two independent variables. A strong organizational culture and inspirational leadership have been proven to foster a productive work environment that positively impacts employee performance.